Ethnomathematic Value in Traditional Building in Kampung Budaya Bogor Jawa Barat - Bahagia Bahagia; Rimun Wibowo; Leny Muniroh; Azhar Al-Wahid; Rizkal Rizkal; Zakky Muhammad Noor (Mathematics Education Study Program, 2022)
Mathematic value in traditional building have been overdued typically for traditional building in sundaness tribe. The goal of this research to discover ethnomathematics value in some building of sunda in kampung budaya in Bogor West Java. This study uses a qualitative method. The sampling technique was carried out purposively, namely the head of kampung Budaya and the key person of kampung budaya sunda sindang Barang Bogor Jawa Barat. Data were collected by in-depth interviews. The sample was selected through a purposive technique. The results were carefully examined through triangulation and source triangulation techniques. The results show that in leuit as the place for saving paddies contain numerous ethnomathematical including in the leuit building, especially on the roof of leuit which is in front there are mathematical elements such as a triangle facing each other but in the middle between the two there is a square and there is an equilateral triangle. While in traditional Sundanese houses there is woven on the walls where the wicker contains mathematical values ​​ranging from straight lines, parallel lines, perpendicular lines, and horizontal lines. Besides that, on the door, there are four right triangles where one pair is opposite, but the other pair is positioned upside down to the other.